Wedded to war : a novel - Green, Jocelyn (Green, Jocelyn. Heroines behind the lines: Civil War., 2012)
"This is the first book in a series based on the real life stories of women who lived and worked during the Civil War. The author has done extensive research around the lives of military women during the Civil War for a nonfiction title and became inspired to share their stories in a fictionalized depiction based on her historical research. Charlotte Waverly is a 28 year-old upper-class woman from New York and one of only 100 women chosen for nursing training. On the battlefields, she and the other nurses find themselves up against corruption, opposition and wounded men such as they have never seen before. Charlotte's life intersects with that of an Irish immigrant who turns to the unthinkable when faced with starvation after her husband leaves for war. These women find hope and gain restored lives as war wages all around"--